Exploring the importance, meaning and experience of hope for adult patients with advanced cancer and their family caregivers in KwaZulu-Natal - Cox, Colleen (Division of Public Health, 2024)
Background: The importance of hope for patients with cancer and other life-threatening illness has been widely reported in international literature. Hope enhances patients' quality of life and facilitates coping. Towards end-of-life, hope is typically directed at “being” rather than at “doing”, and at preparing for a peaceful death. Patients and their families reportedly look to healthcare professionals to give them hope. In South African palliative care settings, patients describe their need for psychosocial and spiritual care and for their hope to be upheld. There is however not a clear understanding of what hope means in the South African healthcare setting, particularly around issues such as “hope for a cure” and “false hope”. Also, while several hope-fostering interventions have been validated internationally, the benefits of such interventions in South Africa are unknown. Aim: The study aimed to describe the importance, meaning and experience of hope for adult patients with advanced cancer and their family caregivers in KwaZulu-Natal (KZN). Method: Two study sites in KZN were chosen, a state hospital oncology unit and a hospice. The study followed a qualitative descriptive cross-sectional design, involving in-depth analysis of semistructured interviews with patients with advanced cancer and their family caregivers. Each patient and their family caregiver were managed as a dyad. Questions around the importance, meaning and experience of hope were explored. Data collection continued via purposive sampling until data adequacy was achieved. Data were coded and analysed thematically. Data were also analysed in the context of the clinical, socio-economic and cultural contexts of the patients and their caregivers. Results: The study sample included 11 patients and 11 family caregivers. Purposive sampling achieved variance in most clinical and socio-economic factors. Identified limitations of the study however included the lack of young adults in the study sample, and that each study participant had a religious affiliation, either Christian, African Ancestral, Hindu or Muslim. Despite wider screening, there were no atheist or agnostic participants. There was unanimous affirmation from all patients and caregivers that hope was important to them, particularly in the face of a cancer diagnosis or caregiving role. Thematic analysis of the meaning of hope revealed a strong correlation with spirituality, human connection and support, and physical and psychological comfort. Hope was also associated with psychological fortitude, having a goal and purpose, and living well while being ready to die. The study demonstrated the tension of oscillating between hoping for a cure and accepting a poor prognosis. As with meaning, the hope experience was strongly influenced by spirituality, human connection and support, and physical and psychological comfort. The role of overcoming previous adversity as a source of hope for most participants was an unexpected finding. Almost all participants expressed a preference for truthful communication regarding their diagnosis or prognosis and described how hope assisted them to cope with bad news and to reach acceptance. Participants described how doctors and nurses can give hope to patients and families. Conclusion: The study confirmed the importance of hope in assisting patients with cancer and their family caregivers to cope and to live well in the face of life-threatening illness. Interventions including H - human connection and support, O - (reflections on) overcoming previous adversity, P - physical and psychological comfort, and E - existential or spiritual support, are expected to enhance hope for patients with cancer and their family caregivers in the South African setting. Further research to validate hope-fostering interventions in South Africa is recommended